(untitled) (The Batuk, 2023)
The research work has been conducted to examine the impact of age, total expense, total investment, and turnover ratio on financial performance of mutual funds in Nepal. Out of 29 mutual funds reported by Nepal Stock Exchange Ltd (as on 15 January, 2022), a total of 10 mutual funds following judgmental sampling technique have been selected as sample of the study. Samples are selected with the objective of getting 32 months data (from 12-Feb 2019 to 16-Sep 2021) resulted 320 observations. The required balanced panel data have been extracted from the monthly reports published on respective websites. Based on the regression result, it has been found that the age, total investment and turnover ratio have significant positive impact on net asset value but the magnitude of turnover ratio is negligible. However, impact of total expense on net asset value is positive but not found significant. The result can give mutual fund managers an insight on improving funds performance. On the other hand, the result can be helpful to investors in deciding their investment on mutual funds. Analysis with adding more variables will be beneficial in increasing the generalizability of the findings.